EFFECTS OF SEED INOCULATION WITH Azospirillum brasilense AND NITROGEN DOSE ON OIL CONTENT OF CORN GRAINS - Dias, Vanderlan Carneiro; Peluzio, JoÃªnes Mucci; Lima, Maria Dilma de (REVISTA DE AGRICULTURA, 2019)
ABSTRACTÂ Due to its high economical importance and the need of high amounts of nitrogen fertilizer, the corn crop demands further and deeper studies on biological nitrogen fixation trough bacterium Azospirillum brasilense. Therefore, this study aimed at assessing influence of inoculation of three different genotypes (Orion, A1 Bandeirante and AG-1051) with such bacterium in association with cover application of five different nitrogen doses on percentage oil content in the grains. Data were subjected to ANOVA and means compared by Tukey test at 5%. The inoculation of A. brasilense, with or without nitrogen fertilization, has promoted oil content increase in the grains. Orion genotype presented the greatest increase with the bacterium inoculation, as well as it was the most productive at the lowest nitrogen dosages assessed. High temperatures favored the increase in the oil content in the grains. Â Keywords: Zea mays, inoculation, biological fixation, oil Â EFEITOS DA INOCULAÃ‡ÃƒO COM Azospirillum brasilense E DOSE DE NITROGÃŠNIO SOBRE O TEOR DE Ã“LEO DE MILHO Â RESUMO Devido Ã sua grande importÃ¢ncia econÃ´mica e necessidade de fertilizantes nitrogenados, a cultura do milho exige estudos mais aprofundados sobre a fixaÃ§Ã£o biolÃ³gica do nitrogÃªnio pela bactÃ©ria Azospirillum brasilense. Portanto, este estudo teve como objetivo avaliar a influÃªncia da inoculaÃ§Ã£o de trÃªs diferentes genÃ³tipos (Orion, A1 Bandeirante e AG-1051) com essa bactÃ©ria em associaÃ§Ã£o com a aplicaÃ§Ã£o de cinco diferentes doses de nitrogÃªnio no teor percentual de Ã³leo nos grÃ£os. Os dados foram submetidos Ã ANOVA e as mÃ©dias comparadas pelo teste de Tukey a 5%. A inoculaÃ§Ã£o de A. brasilense, com ou sem adubaÃ§Ã£o nitrogenada, promoveu aumento do teor de Ã³leo nos grÃ£os. O genÃ³tipo Orion apresentou o maior aumento com a inoculaÃ§Ã£o da bactÃ©ria, bem como o mais produtivo nas menores dosagens de nitrogÃªnio avaliadas. As temperaturas altas favorecem ou aumentam o teor de Ã³leo nos grÃ£os. Â Â Â Â Â Â Â Â Â Â Â Palavras-chave: Zea mays, inoculaÃ§Ã£o, fixaÃ§Ã£o biolÃ³gica, Ã³leo